Internationalization of Entrepreneurial Ventures in Transition Countries - Leković, Božidar Stojan; Marić, Slobodan Milan (Industrija, 2017)
Healthy and flexible economic structure of entrepreneurial ventures and small enterprises is treated as an indispensable part of the economic mosaic and significant element of international competitiveness. The above mentioned aspect of entrepreneurial ventures will be analyzed through the degree of involvement in the process of internationalization in the context of regional and global integration processes as the last stage of the economic aspects of the globalization process by observing the level achieved in the context of transition countries in comparison with other groups. The main objective of the work is focused on the analysis of the involvement of the entrepreneur in the process of internationalization of operations depending on the stage of economic development of the group of countries and the stage reached in the development of the entrepreneurial process. Thus, the available data of the GEM project allow the analysis and identification of a potential specific group of transition countries compared to other countries with different development levels in terms of the achieved level of involvement in the process of internationalization of entrepreneurial ventures, by using the application of statistical methods for determining differences between groups using MANOVA, Anova, discriminant analysis and Mahalanobis distance. The results of research will directly set goals in terms of the degree of involvement of the entrepreneur in the process of internationalization of operations depending on the achieved level of economic development and the stages in the development of the entrepreneurial process, singling out specific countries in transition.
Keywords: transition; internationalisation; entrepreneurial venture; small business